Impact of local anesthesia on ciliary dyskinesia diagnosis by digital high‐speed videomicroscopy - Benchimol, Lionel; Bricmont, Noemie; Bonhiver, Romane; Hans, Grégory A.; Lefebvre, Philippe; Kempeneers, Celine; Poirrier, Anne‐Lise (Pediatric pulmonology, 2025)
Summary This prospective study investigates the impact of local anesthesia on ciliary function in nasal epithelium. The primary objective was to assess whether lidocaine 2% and naphazoline 0.5% nasal spray alter ciliary beat frequency and pattern in subjects undergoing nasal brushing, aiming to enhance primary ciliary dyskinesia (PCD) diagnosis. Hypothesis It was hypothesized that local anesthesia administration would not significantly affect ciliary function in nasal epithelium. Study Design A prospective, simple‐blind randomized study was conducted between 2020 and 2023. The study employed digital high‐speed videomicroscopy to analyze ciliary beat frequency and pattern. Patient/Subject Selection A cohort of 38 participants was recruited, consisting of 25 healthy volunteers and 13 referred individuals (including seven diagnosed with PCD). Selection criteria ensured the absence of chronic respiratory diseases, recent respiratory tract infections, or regular use of nasal medications. Methodology Participants underwent nasal brushing with administration of lidocaine and naphazoline nasal spray in one nostril and saline in the contralateral nostril. Ciliary beat frequency and pattern were measured using digital high‐speed video microscopy. Results Nasal spray administration did not significantly alter ciliary beat frequency or pattern compared to saline (p = 0.841 and p = 0.125, respectively). Subgroup analysis revealed consistent results across healthy volunteers, referred patients, and PCD patients. Conclusion Local anesthesia with lidocaine and naphazoline spray did not affect ciliary function outcomes. These findings support the safe use of these agents in clinical practice for PCD diagnostic procedures. Further research with larger cohorts is warranted for validation.